MENGGALI TRANSFORMASI FASADE BANGUNAN DI LORING PASAR KOTAGEDE, YOGYAKARTA, MELALUI SKETSA MANUAL - Augustinus Madyana Putra; Gagoek Hardiman; Agung Budi Sardjono (Sabda: Jurnal Kajian Kebudayaan, 2019)
The identity of a region is an important thing to stay legible for the present and the future. One of the things which play a role in the legibility of the region's identity is the facade of building. This facade is the first component that can be directly observed by the people to get an overall picture of the region. One of the most important historical regions in Yogyakarta is Kotagede. As a result of various demands, there was a change of facade in this region. This study observes the change of facade where it was a group of buildings north side of the Market (Loring Market), a location where Ki Ageng Pemanahan lived in the 16th century.The research method we used is observing the location, interviewing, sketching based on the interviews, and making a more detailed description. The data collected is then analyzed to get a conclusion and to explain the phenomenon in this region.The result shows a change of facade at the Loring Market location. It occurred due to the changes in heirs, the development of functional demands, natural disasters, and the government arrangement. It also led to an adjustment of community responses to the region.